Opportunities and challenges for converged platform for audio-visual and data services in 470-790 MHz UHF broadcasting band - Lei Shi; Ki Won Sung; Jens Zander (International Telecommunications Society (ITS), 2013)
In this paper, we will investigate the potential opportunities and challenges for deploying a converged platform in the UHF Broadcasting band (470-790 MHz) to replace the legacy systems and provide terrestrial audio-visual and dataservice. As recent development shows, both mobile broadband and terrestrial broadcasting (DTT) now overlap to offer audio-visual services to customers. Whereas DTT is designed only for audio-visual content, mobile broadband systems are converged all-IP platforms that may carry a multitude of services in unified and device-agnostic way. DTT used to be highly effective, when the task was to distribute a few TV channels to large audiences. However, for the rapidly increasing long-trail of niche television channels, each with diminishingly few viewers, DTT is no longer an efficient way of using the spectrum. Progressively re-farming of the UHF broadcasting band for more flexible and efficient use, is high on the list of discussion items in the upcoming World Radio Conference 2015, it is highly relevant to evaluate this option with a holistic view. This paper will present findings from the analysis of the inherent strengths and weaknesses of mobile and broadcasting industries in their new roles in the converged ecosystem. Detailed discussions are focused on identifying the possible benefits and threats from the perspectives of the broadcasters, mobile network operators, digital terrestrial network operators and the society as a whole. Overall we consider such a converged platform is a win-win solution for most of the stakeholders thanks to the increase in spectrum and network efficiency and flexibility improvement in the all-IP network. Nevertheless, there are still challenging issues to be addressed, such as the compensation and new business model for the digital terrestrial network operator and ensuring the quality of service for audio-visual content delivery in cellular network.
Keywords: 330; Convergence; DTT broadcast; mobile broadband; UHF broadcasting band